Work Values of Chinese MPA Students: Underlying Dimensions and Group Differences. Issue 7 (19th May 2021) - Bao, Yuanjie; Zhong, Wei
ABSTRACT: The empirical examination of MPA students' work values is scant. Surveying 277 full-time and part-time MPA students from a Chinese public administration school, the present study investigated the underlying dimensions of work values and how those dimensions are emphasized differently by students who differ on gender, career preferences, and affiliations. Six underlying dimensions of work values were revealed, and significant gender differences were found on three of the six dimensions. Furthermore, full-time students who prefer government career over business career and part-time students from government and para-government sectors showed their preferences on different dimensions. Theoretical and practical implications are discussed.